The Effect Of Mouthwashes On Color Change In Universal Composite Resin - Pratiwi, Deviyanti; Natanael, Christian; Liliany Margaretta, Dewi; Tjandrawinata, Rosalina; Suwandi, Trijani (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
Background: The use of mouthwash has increased and become a habit since the Covid-19 pandemic. The use of mouthwash is recommended for prevention. The mouthwashes that American Dental Association (ADA) and Center for Disease Control and Prevention (CDC) recommended are chlorhexidine gluconate (CHX), hydrogen peroxide (H2O2), cetilpyridinium chloride (CPC), povidone iodine (PVP-I), dan chlorine dioxide (ClOâ‚‚). Universal composite resin is used for every tooth color requirement and has a chameleon effect that can disguise, eliminate, minimize, and neutralize mismatched colors. This study aims to determine various mouthwashesâ€™ effects on the discoloration of universal composite resin. Method: This research is an experimental laboratory by comparing the color changes before and after treatment. Thirty samples of universal composite resin with a width of 10 mm and a height of 2 mm were divided into 5 mouthwash test groups and 1 control group. Color test using a Vita Easy Shade V spectrophotometer and the data were shown in DE assessment. Result: Data were analyzed with One Way ANOVA on DE assessment with the significance level p<0.05 on 5 test groups. Conclusion: The 5 groups of mouthwashes showed there was a color change in the DE assessment of universal composite resin